Ophiocordyceps sinensis: a prominent source of bioactive components for alleviating overactive bladder - Pang, Li-Yin; Tan, Chon-Seng; Ng, Szu-Ting; Lim, Kuan-Hon; Then, Sue-Mian; Kang Nee, Ting (Life Sciences, Medicine and Biomedicine, 2020)
Ophiocordyceps sinensis is one of the most sought-after medicinal fungi used to treat various medical conditions such as respiratory diseases, liver and kidney dysfunctions. In China, it is widely used for alleviation of frequent urination where patients treated with O. sinensis have shown improvement in nocturia, which is the most common symptom of overactive bladder (OAB). Many studies have reported its anticancer, anti-inflammatory, anti-oxidative, hypoglycaemic and vasorelaxation properties. These properties are attributable to the presence of bioactive components such as polysaccharides, proteins and nucleosides. This mini-review highlights the medicinal potential of O. sinensis in alleviating OAB, which is a debilitating condition with a profound impact on the quality of life in a high proportion of older people. Four possible mechanisms of action of O. sinensis are suggested. Firstly, the relaxation of bladder smooth muscle through calcium dynamic, production of nitric acid (NO) and adenosine triphosphate (ATP). A second mechanism proposed is through the suppression of micturition reflex. The unequivocal properties of O. sinensis as anti-inflammatory and anti-oxidant, are two other plausible explanations, as both chronic inflammation and accumulation of oxidative stress molecules are associated with OAB exacerbation. With the recent success in cultivation of O. sinensis and the positive results from toxicity studies, a better understanding of its pharmacological actions can be further substantiated, including its use for relieving OAB.